Noteworthy Insights at the Personal and Community Level – people with mental health difficulties and meaningful social spaces - Kass, Kadi; Narusson, Dagmar (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2025)
Objective: The core value underlying this study is social inclusion. This paper studies how people with mental health difficulties find meaningful everyday life and identity as members of the community. The study focuses on the experiences and perspectives of individuals with mental health difficulties and their view and interpretation of connections with spaces, places, and people in the communities. It is essential to include their voices and actively involve them in the research process to comprehensively understand their needs, preferences, and goals concerning community-based recovery.Research Design and Methods: The research exhibits novelty in two fundamental aspects:18 persons with mental health difficulties participated as co-researchers, and for data collection, creative methods were used (creative writing, photovoice, etc.). Co-researchers live in apartment buildings in ordinary neighbourhoods and receive supported housing services in three Estonian cities.The data was analyzed using thematic analysis. The study combined creative methods such as diary entries, collages, or photovoice to include the first-person perspectives. Involving people with mental health difficulties acting as co-researchers is an innovative approach to this study.Results: The results identify the effect social interaction and visiting various places in the community can have on people. A place will have a deeper meaning for the person visiting when it relates to memories, emotions, supporting people, and likeable activities they can do there.Conclusions: It is important for the recovery process that people with mental health difficulties spend time in an environment that is suitable – flexible, appreciative, and supportive of development for them, providing both visual satisfaction, varieties of activity, and undemanding sociality, i.e. possibility to be connected with other people.